Poland Long-Term Care Regional Spending Review : Pomorskie Region - World Bank (World Bank, Washington, DC, 2020)
Poland is facing an enormous demographic change as the population age at unprecedented pace. Life expectancy is steadily increasing while birth rates for years have remained below simple replacement rate. Access to and quality of long-term care (LTC) services (support for people who are dependent over a long period of time on help with their daily living) will be crucial, especially in the context of the pension reform that implies a significant reduction of replacement rates at retirement and potentially an increased risk of poverty among the older population. The LTC arrangements in Poland, traditionally based on informal family support, will have to be adjusted with increasing role of the public sector, which in turn will have implications for the stability of public finance. The motivation of this work is to provide an extensive review of public and private expenditure on LTC services and other related services provided to old age population (65 ). The focus is on the use and real cost of LTC services and the existing financing arrangements as of 2016 which as a starting point help to picture the scale of challenges up to 2050 using the official demographic projections. This spending review has a regional focus that enables to better grasp the challenges under specific regional circumstances and to conduct the bottom-up analysis with data collected from various sources locally. This study provides a pioneer attempt to estimate costs related to LTC services at the regional (poviat) level looking at two poviats in pomorskie region: wejherowski and człuchowski. The study is organized as follows: chapter I discusses demand for LTC with detailed discussion on demographic prospects for Poland followed by the analysis for człuchowski and wejherowski poviats. Chapter II focus on supply and costs of LTC services; again the overview of LTC services in Poland is followed by the section discussing supply and costs in the two analyzed poviats. Chapter III provides conclusions and discusses the challenges of LTC system in Poland.